2014
DOI: 10.1002/nml.21110
|View full text |Cite
|
Sign up to set email alerts
|

Co‐located Nonprofit Centers

Abstract: Nonprofit centers are organized to house individual nonprofits “under one roof” to enhance their efficiency and effectiveness and to offer shared services to diminish administrative load. This post‐occupancy tenant satisfaction survey of three such US centers represents the first empirical analysis of such organizations. We find that nonprofit tenants (N = 118) initially co‐located due to the leasing price and the new physical environment (free parking and safety). Nearly all nonprofit tenants wished to remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The literature on IOs in the human services has focused on their connections to academic institutions (Austin et al, 1999). In a similar way, the literature on intermediary management service organizations features their importance for supporting the development and sustainability of community collaborations (Connor, Kadel-Taras, & Vinokur-Kaplan, 1999), and their role in supporting fledgling nonprofits in multiorganization nonprofit centers (Vinokur-Kaplan & McBeath, 2014). In contrast, little research has focused on how IOs help transfer knowledge to HSOs despite the existence of a literature on the role of IOs in other sectors such as education (Cooper, 2014).…”
Section: Link Officers As Boundary-spanning-knowledge Brokersmentioning
confidence: 99%
“…The literature on IOs in the human services has focused on their connections to academic institutions (Austin et al, 1999). In a similar way, the literature on intermediary management service organizations features their importance for supporting the development and sustainability of community collaborations (Connor, Kadel-Taras, & Vinokur-Kaplan, 1999), and their role in supporting fledgling nonprofits in multiorganization nonprofit centers (Vinokur-Kaplan & McBeath, 2014). In contrast, little research has focused on how IOs help transfer knowledge to HSOs despite the existence of a literature on the role of IOs in other sectors such as education (Cooper, 2014).…”
Section: Link Officers As Boundary-spanning-knowledge Brokersmentioning
confidence: 99%
“…Attempts to shape the broader physical spaces in which nonprofits operate also matter as evidenced by Bastian and Napieralski (), who point out that the shape of the physical environment forms the need for services provided by nonprofits, as in the case of food desserts, and by Hetling and Botein (), who conducted a case study of external influences on program success using a case study of a program of supportive housing for domestic violence victims and found that physical site characteristics were important external influences. Vinokur‐Kaplan and McBeath () examine nonprofit organizations that colocate to save rent and for the physical security and enhanced work environment provided by the density of organizations and find that the organizations are satisfied with the arrangements and want to continue to work in a colocated setting. In this case, interventions in the physical environment are being made by nonprofits not to directly benefit stakeholders but to improve the physical environments in which they are located, presumably increasing mission attainment and ability to meet stakeholder needs.…”
Section: Relevant Literature: Areas In Which Nonprofits Are Working Tmentioning
confidence: 99%
“…Since the 1980s, global economic restructuring and broader neo-liberal public policy shifts have been reshaping and redefining the responsibilities of nonprofits across rural and small town regions (Tonts & Horsley, 2019). This neo-liberal policy orientation has emphasized market-oriented service provision and infrastructure delivery, while offloading key responsibilities to place greater emphasis on empowering nonprofits to shape their own destiny and mobilize place-based assets.…”
Section: Introductionmentioning
confidence: 99%